Biomarkers as Key Contributors in Treating Malignant Melanoma Metastases - Camila Ferreira de Souza; Alice Santana Morais; Miriam Galvonas Jasiulionis (Dermatology Research and Practice)
Melanoma is a human neurocristopathy associated with developmental defects in the neural crest-derived epidermal melanocytes. At the present time, at least three hypotheses were identified that may explain melanoma aetiology, as follows: (1) a model of linear progression from differentiated melanocytes to metastatic cancer cells (2) a model involving the appearance of melanoma stem-like cells, and (3) an epigenetic progenitor model of cancer. Treating metastatic melanoma is one of the most serious challenges in the 21st century. This is justified because of a subpopulation of cells presenting a remarkable molecular heterogeneity, which is able to explain the drug resistance and the growing mortality rates worldwide. Fortunately, there are now evidences sustaining the importance of genetic, epigenetic, and metabolomic alterations as biomarkers for classification, staging, and better management of melanoma patients. To illustrate some fascinating insights in this field, the genes BRAFV600E and CTLA4 have been recognized as bona fide targets to benefit melanoma patients. Our research attempts to carefully evaluate data from the literature in order to highlight the link between a molecular disease model and the key contribution of biomarkers in treating malignant melanoma metastases.